INTEGRASI HIGH ORDER THINKING SKILLS (HOTS) DALAM LEMBAR KERJA SISWA CERDAS DAN KRITIS BERBAHASA INDONESIA UNTUK KELAS IX SMP/MTs - Muhammad Rizal (Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study is to describe the types and levels of high-level thinking exercises in LKS Teks Tanggapan: Cerdas dan Kritis Berbahasa Indonesia kelas IX SMP/MTs which is the result of the development of teaching materials in 2019. The integration of higher-order thinking skills is expected to provide input to the form of exercises to be designed for text learning to be more meaningful. This research is a qualitative analysis technique using content analysis to infer textual units into conceptual categories. The data form is exposure to nonverbal data of training in LKS. The results showed that there were six out of nine exercises that integrated the thinking processes of C4, C5, and C6 accompanied by additional information to the users of teaching materialsÂ